The role of family support in managing death anxiety among the elderly - Niko Dima Kristianingrum; Yati Sri Hayati; Annisa Wuri Kartika; Fransiska Imavike Fevriasanty; Selsa Rifziqka Heltha Novian Haryono; Ayut Merdikawati (PAGEPress Publications, 2024)
Death anxiety is a sentimental state experienced by individuals, specifically the elderly due to the occurrence of unpleasant events and contemplation of mortality. This condition is primarily caused by a lack of social support from family, which has a significant effect on mental health. Therefore, this study aimed to analyze the correlation between family support and the level of death anxiety in the elderly. The study procedures were carried out with a cross-sectional method, and the sample population comprised 239 elderly who were selected at a community health center in Malang Indonesia using cluster random sampling. Family support was measured using the Family Support Instrument (FSI), while death anxiety level was assessed with the Death Anxiety Scale (DAS). The relationship between the 2 variables was then tested using Spearman's Rank correlation test with p<0.05. The results showed that there was a strong correlation between the 2 variables, with family support falling into the high category for 98 participants (41%). In addition, 117 participants (49.0%) were reported to have a low category of death anxiety level. To conclude, these findings could be applied and used as a reference for future studies by exploring variables and conditions influencing family support and the death anxiety level of the elderly.